Petroleum exploration and production in Nigeria: a blessing or a curse? (2023)
Oil exploration in Nigeria started in 1903; however, drilling activities started in 1951. In 1956, Shell-British Petroleum (BP) made a significant discovery of oil in the Oloibiri community (present-day Bayelsa State). Crude oil production began in 1957, and in 1960, 849,075 tonnes of crude oil were exported. To date, approximately 1,500 exploration wells have been drilled, with most of these being onshore, whereas the rest are in shallow offshore and deepwater. The exploration success rate has increased primarily due to three- dimensional seismic and sequence stratigraphy advancements. Oil and gas exports contribute significantly to Nigeria's economy, mainly federal government revenue and foreign exchange earnings. In this Chapter, the authors have examined the history of oil exploration in Nigeria, operating agreements, contributions of oil and gas to Nigeria's economy, the Petroleum Industry Act (PIA) (as the new framework for participation and regulation) and challenges faced during oil exploration and production in the country.